Azole borate crystal and preparation method thereof, and boron nitride material prepared by pyrolysis of azole borate precursor

The azole carbamate crystals prepared in supersaturated solution, combined with pyrolysis technology under high temperature direct nitrogen environment, solve the complexity and safety hazards of existing borate precursors in the preparation of hexagonal boron nitride, and achieve efficient and safe preparation of boron nitride materials, expanding its application scope.

CN119824546AActive Publication Date: 2025-04-15HEBEI UNIV OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411942005.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-15
Estimated Expiration
2044-12-27

AI Technical Summary

Technical Problem

The existing borate precursors have problems such as complex synthesis, high safety hazards for pyrolysis, low solubility and many impurities for pyrolysis products when preparing hexagonal boron nitride (h-BN), which limits the industrial production and application of h-BN.

Method used

The 3-amino-1,2,4-triazole or 3,5-diamino-1,2,4-triazole is used as the nitrogen source and the boron-containing compound in a supersaturated solution to prepare the boron nitride material by pyrolysis under high temperature direct nitrogen environment.

Benefits of technology

The high solubility, high purity and gentle synthesis and pyrolysis process of boric acid azole crystals have been achieved, the preparation of boron nitride precursors has been significantly optimized, the production efficiency, safety and application range have been improved, and it is suitable for the large-scale production of high-purity hexagonal boron nitride materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119824546A_ABST
    Figure CN119824546A_ABST
Patent Text Reader

Abstract

The invention relates to an azole borate crystal and a preparation method thereof, and a boron nitride material prepared by pyrolysis of an azole borate precursor. And the product with the single crystal particle size of not less than 1mm and the particle size of the single crystal aggregate of not less than 1cm can be prepared. The two crystals are named as a crystal ZB and a crystal AB respectively, the chemical formulas of the crystals are [C4H11N10] [B5O6 (OH) 4] and [C2H5N4] [C2N4H4B5O6 (OH) 4] respectively, and the crystals have definite chemical characteristics that the molecular weight of the ZB is 417.31, the ZB belongs to a monoclinic system, the space group is Ia, and the cell parameter is # imgabs0 # Z = 4; the molecular weight of AB is 387.27, AB belongs to a triclinic system, the space group is P-1, and the cell parameter is # imgabs1 # Z = 2. In view of the fact that the boric acid azole crystals can be directly pyrolyzed and converted into hexagonal boron nitride at a high temperature in an inert atmosphere and have high solubility, good melting characteristic and viscosity during solution concentration, the boric acid azole crystals are used as precursor materials, are suitable for preparing various types of hexagonal boron nitride materials, and are efficient and suitable for large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical field:

[0001] The invention relates to the technical field of growth of synthetic crystals and pyrolysis preparation of precursors of boron nitride ceramics, and in particular to a boric acid azole crystal and a preparation method thereof, and a boron nitride material prepared by pyrolysis of a boric acid azole precursor. Various types of boron nitride materials are prepared by pyrolysis of boric acid azole. Background technology:

[0002] Hexagonal boron nitride (h-BN), with its unique physical and chemical properties, has shown extensive and far-reaching application potential in the field of materials science, not only limited to high-temperature lubricants, ceramic reinforcements, electronic packaging materials, but also an important precursor in the field of two-dimensional materials. However, the synthesis of high-quality h-BN depends largely on the selection and pretreatment of the precursor, which requires the precursor to have high pyrolysis efficiency and extremely low impurity content, while ensuring the operability, controllability and environmental friendliness of the process.

[0003] Although many borates have been explored as precursors for the preparation of h-BN, each material has obvious limitations, which seriously restricts the large-scale industrial production of h-BN and the further expansion of its application fields. The following is an in-depth analysis of several typical precursors and the challenges they face: (1) Ammonia borane complex: As one of the first h-BN precursors studied, the pyrolysis of ammonia borane can indeed effectively generate h-BN. However, its violent decomposition at high temperatures, accompanied by the release of a large amount of hydrogen, not only greatly increases the safety risk during operation, but also puts forward more stringent requirements on production equipment, increasing production costs and safety management difficulties. In addition, the synthesis path of ammonia borane is complex and requires strict control of conditions to avoid the potential dangers brought by the byproduct hydrogen, further aggravating the production difficulty and cost burden. (2) Melamine·2-boric acid adduct: Although the formation of this phase is relatively easy, it is quite difficult to obtain high-purity and high-crystallinity crystals. Its extremely low solubility in conventional solvents limits its application potential in the pyrolysis synthesis of multi-morphological and multi-structural h-BN. After pyrolysis, a single porous boron nitride fiber material is mainly formed, which poses a significant obstacle to the development of other types of boron nitride materials. (3) Guanidine borate salts: The synthesis of guanidine borate also faces the problem of complexity, which is mainly reflected in the uncontrollable defects in the crystal growth process, often resulting in a powder product mixed with multiple guanidine borate phases, which brings new challenges to phase purification. In addition, it is difficult to grow guanidine borate crystals into large-sized single crystals, and most guanidine borate crystal phases have low solubility in many common solvents, which greatly limits its application as a precursor in the preparation strategy of diversified pyrolytic boron nitride. (4) Boric acid imidazole salts: Although the structure of imidazole borate is conducive to the formation of h-BN, its synthesis route is lengthy and costly, and it is easy to produce carbon pollution during the pyrolysis process, which affects the purity of the final product.

[0004] In summary, existing precursors generally have problems such as complex synthesis, high safety risks in pyrolysis, low solubility, and many impurities in pyrolysis products. Therefore, the development of new hexagonal boron nitride precursor crystal phases must have the characteristics of simple synthesis, safe and controllable pyrolysis process, excellent solubility and high purity of pyrolysis products. It is of vital strategic significance to overcome the shortcomings of existing precursors and promote the widespread application and development of h-BN in solution-based preparation technology. Future research should focus on exploring new precursor materials, optimizing synthesis routes, improving pyrolysis efficiency and product purity, while paying attention to environmental friendliness and reducing production costs, so as to comprehensively promote the progress of h-BN material science and industrial upgrading. Summary of the invention:

[0005] The object of the present invention is to provide a boric acid azole crystal and a preparation method thereof, and a boron nitride material prepared by pyrolysis of a boric acid azole precursor.

[0006] To achieve the above object, the technical solution adopted by the present invention is:

[0007] In a first aspect, the present invention provides a boric acid azole crystal, denoted as boric acid azole crystal ZB, wherein the chemical formula of the boric acid azole crystal is [C4H 11 N 10 ][B 5 O6(OH)4], molecular weight is 417.31, belongs to monoclinic system, space group is Ia, unit cell parameters are: unit cell edge lengths are The angles between the unit cell edges are α = 90°, β = 90.7880(10)°, γ = 90°; Z = 4; the unit cell volume is

[0008] In the second aspect, the present invention provides a boric acid azole crystal, denoted as boric acid azole crystal AB, the chemical formula of the boric acid azole crystal is [C2H5N4][C2N4H4B5O6(OH)4], the molecular weight is 387.27, belongs to the triclinic system, the space group is P-1, and the unit cell parameters are: the unit cell edge lengths are respectively The angles between the unit cell edges are α = 92.699 (2) °, β = 98.516 (2) °, γ = 107.985 (2) °; Z = 2; the unit cell volume is

[0009] The two types of boric acid azole crystals are prepared by using 3-amino-1,2,4-triazole or 3,5-diamino-1,2,4-triazole as a nitrogen source, and the nitrogen source and the boron-containing compound are prepared by a supersaturated solution growth method.

[0010] In the raw materials of the boric acid azole crystal, the molar ratio of nitrogen atoms to boron atoms in the nitrogen source and the boron-containing compound is 2-5.

[0011] In the present invention, the boric acid azole crystals or the agglomerated particles formed by the single crystals can be referred to as boric acid azole particles. The preparation method of the boric acid azole particles is to adopt a supersaturated solution growth method of a nitrogen source and a boron-containing compound to prepare them, comprising the following steps:

[0012] (1) dissolving a mixture of a nitrogen source and a boron-containing compound in a solvent at a target dissolution temperature at one time, and stirring until the reaction is complete to obtain a light yellow, clear, transparent solution;

[0013] Wherein, the nitrogen source is 3-amino-1,2,4-triazole or 3,5-diamino-1,2,4-triazole, and the molar ratio of nitrogen atoms to boron atoms in the nitrogen source and the boron-containing compound is 2 to 5;

[0014] wherein the solvent is capable of dissolving the nitrogen source and the boron-containing compound at a target dissolution temperature;

[0015] The ratio of the total mass (in grams) of the nitrogen source and the boron-containing compound to the volume (in milliliters) of the solvent is in the range of 0.5-2.

[0016] (2) setting a cooling target temperature, cooling the solution obtained in step (1) to the cooling target temperature within a cooling rate range of 0.1° C. / min-10° C. / min, wherein the solution reaches a supersaturated state during the cooling process, and the solution is allowed to grow at a constant temperature at the cooling target temperature until single crystal particles or agglomerated particles formed by single crystal particles grow at the bottom of the solution in the container and the side wall of the container, namely, boric acid azole particles;

[0017] Alternatively, a target evaporation temperature is set, the solution obtained in step (1) is transferred to a container with an opening for circulation, and the solution is heated to the target evaporation temperature. The solvent is slowly evaporated during the heating process. As the solvent continues to evaporate, the solution reaches a supersaturated state. The solution is allowed to stand at a constant temperature and grow at the target evaporation temperature. During the standing process, the solvent is kept in a volatile state until single crystal particles or agglomerated particles formed by single crystal particles grow at the bottom of the solution in the container and the side wall of the container, namely, boric acid oxazole particles.

[0018] Wherein, the cooling target temperature is lower than the dissolving target temperature.

[0019] The preparation method of the present invention is to perform constant temperature static growth at a cooling target temperature, during which the container containing the solution is kept sealed and does not cause any solvent to volatilize.

[0020] The average size of the single crystal particles grown by the preparation method of the present invention exceeds 1 mm, and the agglomerated particles formed by the single crystal particles are not less than 1 cm;

[0021] If the preparation method of the present invention is to perform constant temperature static growth at the evaporation target temperature, the size of the single crystal particles is not less than 1 mm, and the agglomerated particles formed by the single crystal particles are also not less than 1 cm.

[0022] The boron-containing compound in step (1) of the present invention is at least one of boric acid, boron trioxide or sodium borate (borax);

[0023] The solvent in step (1) of the present invention is at least one of water, N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAC) or ethylene glycol methyl ether.

[0024] The borate azolate crystal material is used to prepare boron nitride material.

[0025] In a third aspect, the present invention provides a boron nitride material obtained using the above-mentioned boric acid azole crystals or the boric acid azole particles obtained by the preparation method as a raw material.

[0026] The boric acid azole crystals described above or the boric acid azole particles obtained by the preparation method are used as raw materials, and the boron nitride material is obtained by pyrolysis in a high-temperature direct nitrogen environment, aiming to utilize the pyrolysis process of the boric acid azole material to prepare hexagonal boron nitride, thereby realizing the use of the boric acid azole crystals or particles.

[0027] The obtained boric acid azole crystals or boric acid azole particles of the present invention have the following characteristics:

[0028] Boric acid azole crystals have the property of melting into a fluid melt in the temperature range of 150-250°C;

[0029] The solution of oxazole borate has the characteristic of changing into a viscous and fluid liquid state as the solvent evaporates within the temperature range of 90-250°C.

[0030] A typical feature of the present invention is that the boron nitride material prepared by utilizing the above two features is boron nitride foam or boron nitride fiber.

[0031] In terms of synthesizing boron nitride, the present invention utilizes the obtained boric acid azole crystals or boric acid azole particles to be dissolved in a solvent within a temperature range of 25-150° C. to form a boric acid azole solution with the boric acid azole particles as a solute and a concentration ranging from 1wt.% to 15wt.%;

[0032] Wherein, the solvent is at least one of water, formic acid, acetic acid, methanol, ethanol, isopropanol, DMAC, diethanolamine, triethanolamine, or propylene glycol, ethylene glycol, ethylene glycol methyl ether, dimethyl sulfoxide or tert-butyl alcohol;

[0033] Next, a high molecular polymer is added to the boric acid azole solution for mixed dissolution to form a mixed liquid;

[0034] The mass ratio of the mass of the high molecular weight polymer (in grams) to the mass of the mixed liquid (in grams) is in the range of 1 wt.% to 15 wt.%;

[0035] Wherein, the high molecular polymer is at least one of polyvinyl alcohol, polyethylene oxide, polyethylene imine, polyvinyl pyrrolidone, polyacrylonitrile, polycaprolactone, polyether sulfone, polyimide, chitosan, polyether ether ketone or cellulose;

[0036] Finally, the mixed liquid is spun at a temperature range of 25-80° C. to form a continuous fiber precursor, and the precursor is pyrolyzed at a temperature range of 800-1600° C. for 1-4 hours in a nitrogen environment containing ammonia to obtain a continuous fiber material of boron nitride;

[0037] The nitrogen environment with ammonia is a mixed gas environment of ammonia + nitrogen with an ammonia volume content ranging from 10 vol.% to 100 vol.%.

[0038] Compared with the previous boron nitride precursor material or crystal type, the beneficial effects of the present invention are as follows:

[0039] The synthesis of the precursor ammonia borane complex faces many challenges, especially the problem of solvent selection and solubility. In the traditional method, sodium borohydride is easily hydrolyzed in aqueous solvents, so it is necessary to turn to non-aqueous solvents such as dioxane, tetrahydrofuran or acetone. However, the solubility of sodium borohydride and the generated ammonia borane in these solvents is low, resulting in mixed product precipitation, difficult separation, and low yield, which seriously affects the efficiency and economy of subsequent pyrolysis preparation of boron nitride.

[0040] In contrast, the boric acid azole crystals (ZB and AB) proposed in the present invention have significant advantages. They are obtained by growing single crystal particles of not less than 1 mm in size by a simple saturated solution method in a conventional aqueous solvent, and the reaction conditions of this process are mild and the crystal yield is high. More importantly, the solubility of these crystals in aqueous solvents is extremely high, which effectively avoids the precipitation of by-products, thereby ensuring the high purity and high yield of the crystals. This characteristic makes the synthesis strategy of the present invention not only efficient, but also economically significant, and very suitable for large-scale production.

[0041] In addition, the traditional process of preparing boron nitride by pyrolysis of ammonia borane complex is accompanied by the release of a large amount of hydrogen, which increases the safety risk of production. However, the precursor pyrolysis process of the present invention is relatively mild, and the byproducts are mainly carbon dioxide, nitrogen and water, which are all safe substances, thus significantly improving the safety of production and the feasibility of mass production.

[0042] Compared with melamine 2-boric acid adduct, although it can also be used to prepare porous boron nitride fibers, its solubility is relatively low, which limits its application in various boron nitride precursor forms. The ZB and AB crystals of the present invention have extremely high solvent solubility, and their solubility in water at room temperature is close to 10g, and their solubility at 80-95°C can be as high as 200g, which is 20 times that of melamine 2-boric acid adduct. Its solubility under standard conditions in ethylene glycol, triethanolamine, diethanolamine or propylene glycol solvents can reach within the range of 5g-10g, its solubility under standard conditions in methanol and ethanol solvents is not less than 4g, its solubility under standard conditions in DMAC solvent is not less than 3g, and its solubility under standard conditions in ethylene glycol methyl ether solvent is not less than 1g; these solubilities are much higher than conventional boron nitride precursor crystal materials. This high solubility makes the crystal of the present invention have significant advantages in preparing various types of boron nitride precursors such as micro-nano fibers, foams, low-porosity fibers and spherical particles, further broadening its application range.

[0043] Compared with guanidine borate salts, the crystalline material of the present invention has higher solubility in a variety of common solvents, which makes it have a wider range of application selectivity. At the same time, the crystal preparation process of the present invention is simple and high in purity, avoiding the mixed crystal phase problem that may occur during the growth of guanidine borate crystals, thereby improving the controllability of the morphology or structure of pyrolytic boron nitride.

[0044] Finally, it is worth noting that in the prior art, due to the relatively low nitrogen content in imidazole or methylimidazole, the growing boric acid imidazole is prone to form a trend of more carbon. This results in the boron nitride obtained after pyrolysis usually containing a higher carbon content, which requires further purification. However, the crystalline material of the present invention has a higher nitrogen content, and almost no carbon impurities remain during the pyrolysis process, which is conducive to the pyrolysis synthesis of high-purity hexagonal boron nitride materials.

[0045] The boric acid azole crystals (ZB and AB) proposed in the present invention have high solubility, high purity and mild synthesis and pyrolysis processes, significantly optimize the preparation of boron nitride precursors, improve production efficiency, safety and application range, and are particularly suitable for large-scale production of high-purity hexagonal boron nitride materials. Description of the drawings:

[0046] In order to more clearly introduce the technical solutions and product types of the present invention, the drawings required for use in the description of the embodiments are briefly elaborated and illustrated below. It should be emphasized that these illustration examples are only part of the embodiments of the present invention. For ordinary technicians in this field, without paying creative work, these are likely to extend and multiply to other similar and related illustration examples. In the event that similar and similar illustrations are used as new creative embodiments, they are deemed to be infringements of the present invention.

[0047] Figure 1 1 is a macroscopic photograph of the crystal ZB and the crystal AB grown in Example 1 and Example 2;

[0048] Figure 2 The XRD patterns of the ground powder of the crystal ZB of Example 1 and the XRD patterns simulated by single crystal diffraction are compared;

[0049] Figure 3 The anion and cation parts of the asymmetric minimum unit of the crystal ZB of Example 1 and their combination schematic diagram;

[0050] Figure 4 The XRD patterns of the boron nitride products obtained from the crystal ZB of Example 1 at different pyrolysis temperatures;

[0051] Figure 5 The actual photograph of the crystal ZB after direct pyrolysis in Example 1 is compared with the actual photograph of the crystal ZB before pyrolysis;

[0052] Figure 6 The XRD pattern of the ground powder of the crystal AB in Example 2 and the XRD pattern simulated by single crystal diffraction are compared;

[0053] Figure 7 The anion and cation parts of the asymmetric minimum unit of the crystal AB of Example 2 and their combination schematic diagram;

[0054] Figure 8 The XRD patterns of the boron nitride products obtained from the crystal AB of Example 2 at different pyrolysis temperatures;

[0055] Fig. 9 The comparison of the actual pictures of the crystal ZB in Example 2 before and after pyrolysis;

[0056] Fig.10 This is a SEM photo of a boron nitride nanofiber product obtained by pyrolysis of a continuous fiber precursor prepared using crystalline ZB as a raw material in Example 3;

[0057] Fig.11 This is a SEM photo of a boron nitride nanofiber product obtained by pyrolysis of a continuous fiber precursor prepared using crystal AB as a raw material in Example 4;

[0058] Fig.12 The boron nitride foam product is obtained by pyrolysis using crystalline AB particles as a precursor in Example 5;

[0059] Fig.13 This is an optical electron microscope photograph of the fiber precursor of Example 9. Specific implementation method:

[0060] In order to facilitate understanding by those skilled in the art, the present invention is further described below in conjunction with embodiments. It is necessary to point out here that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some improvements and adjustments made by those skilled in the art to the present invention based on the contents of the present invention still fall within the scope of protection of the present invention.

[0061] Unless otherwise defined, the professional terms used in the present invention are consistent with the meanings commonly understood by those skilled in the art. The raw materials, reagents, instruments, equipment and some consumable materials used in the present invention can be purchased from the market or can be prepared by existing technologies and methods.

[0062] Embodiment 1:

[0063] (1) The preparation method of azole borate single crystal ZB particles is shown in the following steps:

[0064] (a) 99.1 g of 3,5-diamino-1,2,4-triazole (C2H5N5, 1 mol) and 61.8 g of boric acid (H3BO3, 1 mol) were added to 180 mL of deionized water. After complete dissolution by stirring in an oil bath at 95°C for 1 h, stirring and reacting at the same temperature for 2 h, a clear and transparent solution was obtained;

[0065] (b) The transparent solution obtained above was cooled to 45°C at a cooling rate of 5°C / min and kept warm overnight. The solution reached a supersaturated state during the cooling process. The solution was kept at a constant temperature and grown at the target temperature. After 25 hours, the precipitated crystals were taken out and dried in air to obtain single crystal particles ZB. Figure 1 The actual photo of the crystal on the left side of the picture can clearly show that the single crystal particles are agglomerated to form an agglomerated particle assembled with 1mm single crystal as the unit. The size of this agglomerated particle exceeds 1 cm.

[0066] (2) Characterization, single crystal diffraction and analytical analysis of boric acid azole single crystal ZB are as follows:

[0067] The single crystal ZB particles are ground into super powder and the powder XRD pattern is tested (see Figure 2 Select a single crystal particle of ZB and perform single crystal diffraction analysis on a single crystal diffractometer, and use the diffraction data to simulate the XRD spectrum line of the single crystal (see Figure 2 The analysis shows that the two lines are almost completely overlapped, indicating that the single crystal diffraction data can completely resolve the structure of the single crystal. The single crystal diffraction data was analyzed on the OLEX2 software system and the crystal chemical formula was [C4H 11 N 10][B5O6(OH)4], with a molecular weight of 417.31, belongs to the monoclinic system, the space group is Ia, and the unit cell parameters are: the unit cell edge lengths are The angles between the unit cell edges are α = 90°, β = 90.7880(10)°, γ = 90°; Z = 4; the unit cell volume is like Figure 3 The figure shows the smallest asymmetric unit in the unit cell drawn by simulation after crystal ZB analysis. This asymmetric unit consists of anion clusters [B5O6(OH)4] - and cationic clusters [C4H 11 N 10 ] + The combination is formed in the form of hydrogen bonds, where [C4H 11 N 10 ] + It is composed of two asymmetric monomers 3,5-diamino-1,2,4-triazole (C2H5N5) and [C2N5H6] + The two monomers and anionic clusters [B5O6(OH)4] - The crystal chemical formula is [C4H 11 N 10 ][B5O6(OH)4]'s crystal phase.

[0068] (3) Preparation of Boron Nitride Materials by Pyrolysis of Crystalline ZB Particles:

[0069] The obtained agglomerated blocks of crystalline ZB particles were directly placed in a tubular furnace with a nitrogen gas flow rate of 100 mL / min, and the temperature was raised to 800-1500°C at a rate of 5°C / min. After keeping the temperature for 4 hours, the hexagonal boron nitride material was obtained. Figure 4 As shown in the XRD spectrum: Crystalline ZB can be pyrolyzed to obtain boron nitride phase at 800℃, but from the analysis of XRD characteristics, it is believed that the pyrolyzed boron nitride at this temperature stage should belong to staggered boron nitride, but with high purity, and no boron oxide or boric acid impurity phase is detected; with the increase of pyrolysis temperature, after 1100 and 1500℃, the crystallinity of the obtained boron nitride crystal phase is significantly improved, and still maintains extremely high purity characteristics. The impurities of the obtained boron nitride are relatively few, such as Figure 5 The actual photo of the obtained boron nitride shows that the ultra-white body color characteristics illustrate the typical body color characteristics of less or no carbon impurities. Compared with the agglomerated blocks of crystalline ZB particles, the boron nitride after the final pyrolysis also presents blocky structural characteristics, and a bulk material of boron nitride is obtained, which belongs to the hexagonal crystal system.

[0070] Embodiment 2:

[0071] (1) The preparation method of azole borate single crystal AB particles is shown in the following steps:

[0072] (a) 84.1 g of 3-amino-1,2,4-triazole (C2H4N4) and 61.8 g of boric acid (H3BO3) were added to 75 mL of deionized water. After complete dissolution by stirring in an oil bath at 95°C for 1 h, stirring and temperature were maintained constant for 4 hours to obtain a clear and transparent solution;

[0073] (b) The transparent solution obtained above was cooled to 45°C at a cooling rate of 5°C / min and kept warm overnight. The solution reached a supersaturated state during the cooling process. The solution was kept at a constant temperature and grown at the target temperature. After 36 hours, the precipitated crystals were taken out and dried in air to obtain single crystal particles AB. Please view Figure 1 The actual photo of the crystal on the right side of the picture can clearly show that the single crystal particles have been agglomerated to form an agglomerated particle assembled with 1mm single crystal as the unit. The size of this agglomerated particle exceeds 1 cm.

[0074] (2) Characterization, single crystal diffraction and analytical analysis of boric acid azole single crystal AB are as follows:

[0075] The single crystal AB particles are ground into super powder and their powder XRD patterns are tested (see Figure 6 Select a single crystal particle of AB and perform single crystal diffraction analysis on a single crystal diffractometer, and use the diffraction data to simulate the XRD spectrum line of the single crystal (see Figure 6 The analysis shows that the two lines are almost completely overlapped, indicating that the single crystal diffraction data can completely analyze the structure of the single crystal. The single crystal diffraction data was analyzed on the OLEX2 software system and obtained: the crystal chemical formula is [C2H5N4][C2N4H4B5O6(OH)4], the molecular weight is 387.27, it belongs to the triclinic system, the space group is P-1, and the unit cell parameters are: the unit cell edge lengths are The angles between the unit cell edges are α = 92.699 (2) °, β = 98.516 (2) °, γ = 107.985 (2) °; Z = 2; the unit cell volume is like Figure 7 The figure shows the smallest asymmetric unit in the unit cell drawn by simulation after crystal AB analysis. This asymmetric unit consists of an anion cluster [C2N4H4B5O6(OH)4] - and cationic clusters [C4H5N4] + The combination is formed in the form of hydrogen bonds, where [C2N4H4B5O6(OH)4] -A BN coordinated covalent bond is formed in the ion cluster. The formation of this BN bond is a coordination bond formed by the breaking of the N=C double bond on the 3-amino-1,2,4-triazole (C2H4N4) molecule and the bonding reaction with B on [B5O6(OH)4]. Therefore, the two monomers and the anion cluster are hydrogen-bonded to form a crystal phase with a crystal chemical formula of [C2H5N4][C2N4H4B5O6(OH)4].

[0076] (3) Preparation of boron nitride material by pyrolysis of crystal AB:

[0077] The obtained agglomerated block of crystal AB particles is directly placed in a tubular furnace with a nitrogen gas flow rate of 100 mL / min, and the temperature is raised to 800-1500°C at a rate of 5°C / min. After keeping the temperature for 4 hours, the hexagonal boron nitride material is obtained. Figure 8 As shown in the XRD spectrum: Crystal AB can be pyrolyzed to obtain boron nitride phase at 800℃, but from the analysis of XRD characteristics, it is believed that the boron nitride pyrolyzed at this temperature stage should belong to staggered boron nitride, but with high purity, and no boron oxide or boric acid impurity phase is detected; with the increase of pyrolysis temperature, after 1100 and 1500℃, the crystallinity of the obtained boron nitride crystal phase is significantly improved, and still maintains extremely high purity characteristics. The impurities of the obtained boron nitride are relatively few, as shown in the attached Fig. 9 The actual photo of the obtained boron nitride shows that the ultra-white body color characteristics illustrate the typical body color characteristics of less or no carbon impurities. Compared with the agglomerated blocks of crystal AB particles, the boron nitride after the final pyrolysis also presents blocky structural characteristics, and a bulk material of boron nitride is obtained, which belongs to the hexagonal crystal system.

[0078] Embodiment 3:

[0079] Preparation of continuous fiber precursor using crystalline ZB material and preparation of boron nitride continuous fiber by pyrolysis:

[0080] (1) 2 g of ZB crystals were dissolved in a mixed solution of 2 g of polyvinyl alcohol and 25 mL of formic acid. After reacting in an oil bath at 95 °C for 1 hour, the mixture was cooled naturally to room temperature to obtain a viscous spinnable solution, which is a mixed liquid.

[0081] (2) electrospinning the obtained viscous spinnable solution at a spinning voltage of 18 kV and a spinning equipment cavity temperature of 35° C. to obtain a continuous fiber precursor;

[0082] (3) The fiber precursor was placed in a tube furnace, and ammonia gas was introduced at a flow rate of 100 mL / min, a heating rate of 2°C / min, and the temperature was kept at 1100°C for 4 h to obtain the following Fig.10 The boron nitride nanofiber product shown.

[0083] Embodiment 4:

[0084] After replacing the ZB crystal in Example 3 with the AB crystal, the other preparation and pyrolysis processes remain unchanged, and the following can be obtained: Fig.11 The boron nitride nanofiber product shown.

[0085] Embodiment 5:

[0086] Continuous fibers of boron nitride similar to those in the examples can be obtained by replacing the polyvinyl alcohol in Example 3 or Example 4 with polyethylene oxide, polyvinyl pyrrolidone, polyacrylonitrile, polycaprolactone, polyether sulfone, polyimide, chitosan, polyether ether ketone or cellulose.

[0087] Embodiment 6:

[0088] After the AB crystals are ground into fine powder, they are formed into compacted blocks by molding or pressure molds, and the temperature is directly increased to 330°C at a heating rate of 10°C / min under a nitrogen flow of 200 ml / min and kept at this temperature for 1.5 hours, and then the temperature is continued to be increased at a heating rate of 5°C / min to a target temperature of 1100°C, while the nitrogen flow rate is kept constant, and the temperature is kept for pyrolysis for 4 hours, and then the temperature is continued to be increased to 1500°C and kept for pyrolysis in nitrogen for 4 hours to obtain the following Fig.12 The boron nitride foam product shown in the figure. In this embodiment, the characteristic of AB crystal that a fluid melt is formed with a melting point as the temperature rises is fully utilized. Since the temperature rises too fast from 200°C to 330°C, the sample quickly crosses the melting point and is partially decomposed. These two processes occur simultaneously, resulting in the cracking atmosphere bubbling the viscous melt, so that the final pyrolyzed boron nitride presents a foam structure.

[0089] Embodiment 7:

[0090] After the nitrogen in Example 56 is replaced by a mixed gas of nitrogen and ammonia and the crystal AB is replaced by the crystal ZB, while other things remain unchanged, a similar boron nitride foam product can be obtained, and the principle is the same as that of Example 6.

[0091] Embodiment 8:

[0092] Dissolve 10g of crystalline AB particles in 30ml of water. Heat the resulting aqueous solution in an oven at 190 degrees to evaporate the water. After 1 hour, the substance in the oven bubbles to form a foam precursor. The foam precursor is subjected to the same pyrolysis process as in Example 6 or Example 7 to obtain a boron nitride foam material.

[0093] Embodiment 9:

[0094] Dissolve 170g of crystalline AB particles in a 100ml oil bath at 95℃ or above and stir for at least 4 hours. As the water evaporates, a viscous aqueous solution is formed. The viscous aqueous solution is spun under a centrifugal turntable at 200℃ to form a fibrous precursor, such as Fig.13 As shown. After pyrolysis at 1100°C in nitrogen, fibrous boron nitride material can still be obtained.

[0095] Embodiment 10:

[0096] Crystalline AB particles or their ground powder can be thrown out in a centrifugal spinning disk heated to about 180°C to form a fibrous precursor. This fibrous precursor has the properties of crystalline AB, that is, after pyrolysis at 1100°C-1500°C in a high-temperature nitrogen environment, it is still boron nitride and maintains the fiber morphology.

[0097] Examples 11 to 25

[0098] The amounts of 3,5-diamino-1,2,4-triazole and boric acid in Example 1 were respectively changed to the amounts in the following examples, and the amount changes after boric acid was replaced by boron trioxide or borax were shown in the following table:

[0099]

[0100]

[0101] The remaining steps remain unchanged, and the physical phases of the grown precipitate crystals obtained in Examples 14, 15, 19, 20, 24 and 25 are all of the same crystal type as in Example 1. The physical phases of the grown precipitate crystals obtained in other Examples are basically the same as in Example 1, with a small amount of precipitated miscellaneous components of boric acid or sodium borate. This is because there are excessive boric acid groups in the growth solution environment, and the solubility of the nitrogen source is relatively high, causing the balance of the 1:2.5 components in the solution consumed by the growing ZB crystal to gradually deviate more and more obviously, and the excess of boric acid is also more and more obvious. After the supersaturation of boric acid in the supersaturated solution of the final growth is reached in advance, boric acid crystals will gradually grow in the later process of growing ZB crystals, so a trace amount of boric acid crystal phase will be detected, but the dominant content is still the ZB crystal component.

[0102] Embodiment 26

[0103] The amounts of 3-amino-1,2,4-triazole and boric acid in Example 2 were respectively changed to the amounts in the following examples, and the amount changes after boric acid was replaced by boron trioxide or borax were shown in the following table:

[0104]

[0105]

[0106] The remaining steps remain unchanged, wherein the physical phases of the grown precipitate crystals obtained in Examples 29, 30, 31, 34, 35, 36, 39, 40 and 41 are all the same crystal types as those in Example 2. The physical phases of the grown precipitate crystals obtained in Examples 27, 33 and 38 are basically the same physical phases as those in Example 2, but the crystal growth particles are significantly smaller; in Examples 32, 37 and 42, impurities will be precipitated in the later stages of the crystal growth process, most of which are the same AB crystal phases as those in Example 2, and the particles are relatively large, but there is a trace amount of precipitated impurities, which are 3-amino-1,2,4-triazole physical phases, and the particles are relatively small.

[0107] Embodiment 43

[0108] The clear solution in Example 2 was transferred to an open beaker and placed at 50° C. for a long time of more than 48 hours. After the solution evaporated slowly, as the solvent continued to evaporate, the solution reached a supersaturated state, and crystals precipitated and grew on the bottom and side walls of the beaker, obtaining a crystalline substance similar to Example 2.

[0109] Utilizing the methods and techniques of the present invention, indirectly or directly adopting the technical route and basic principles of the present invention to synthesize the corresponding boron nitride product types, and utilizing the prepared hexagonal boron nitride products to apply the technologies and means in other related fields, have the same protection scope as the present invention.

[0110] Without departing from the basic principles, basic raw materials and basic routes of the present invention, any non-inventive technology and process that replaces, simplifies, replaces, modifies, improves, modifies and adds experimental steps and raw materials to produce hexagonal boron nitride products similar to those produced by the present invention, including hexagonal boron nitride fibers, hexagonal boron nitride micro-nano spherical particles or powders, hexagonal boron nitride single crystal sheets and hexagonal boron nitride nanosheets, etc., shall be deemed to infringe upon the present invention.

[0111] Any matters not described in the present invention are applicable to the prior art.

Claims

1. A boric acid azole crystal, which is a boric acid azole crystal ZB, characterized in that: The chemical formula of the boric acid azole crystal is [C4H 11 N 10 ][B5O6(OH)4], with a molecular weight of 417.31, belongs to the monoclinic system, the space group is Ia, and the unit cell parameters are: the unit cell edge lengths are The angles between the unit cell edges are α = 90°, β = 90.7880(10)°, and γ = 90°; the unit cell volume is 2. A boric acid azole crystal, which is a boric acid azole crystal AB, characterized in that: The chemical formula of the boric acid azole crystal is [C2H5N4][C2N4H4B5O6(OH)4], the molecular weight is 387.27, it belongs to the triclinic system, the space group is P-1, and the unit cell parameters are: the unit cell edge lengths are The angles between the unit cell edges are α = 92.699(2)°, β = 98.516(2)°, and γ = 107.985(2)°; the unit cell volume is 3. The boric acid azole crystal according to claim 1 or 2, characterized in that: The boric acid azole crystal uses 3-amino-1,2,4-triazole or 3,5-diamino-1,2,4-triazole as a nitrogen source, and the nitrogen source and the boron-containing compound are prepared by a supersaturated solution growth method.

4. The boric acid azole crystal according to claim 3, characterized in that: The molar ratio of nitrogen atoms to boron atoms in the nitrogen source and the boron-containing compound is 2-5.

5. A method for preparing boric acid azole particles, characterized in that: The preparation method comprises the following steps: (1) dissolving a mixture of a nitrogen source and a boron-containing compound in a solvent at a target dissolution temperature at one time, and stirring until the reaction is complete to obtain a light yellow, clear, transparent solution; The nitrogen source is 3-amino-1,2,4-triazole or 3,5-diamino-1,2,4-triazole, and the molar ratio of nitrogen atoms to boron atoms in the nitrogen source and the boron-containing compound is 2 to 5; the solvent can dissolve the nitrogen source and the boron-containing compound at a target dissolution temperature; The ratio of the total mass (in grams) of the nitrogen source and the boron-containing compound to the volume (in milliliters) of the solvent is in the range of 0.5-2. (2) setting a cooling target temperature, cooling the solution obtained in step (1) to the cooling target temperature within a cooling rate range of 0.1° C. / min-10° C. / min, wherein the solution reaches a supersaturated state during the cooling process, and the solution is allowed to grow at a constant temperature at the cooling target temperature until single crystal particles or agglomerated particles formed by single crystal particles grow at the bottom of the solution in the container and the side wall of the container, namely, boric acid azole particles; Alternatively, a target evaporation temperature is set, the solution obtained in step (1) is transferred to a container with an opening for circulation, and the solution is heated to the target evaporation temperature. The solvent is slowly evaporated during the heating process. As the solvent continues to evaporate, the solution reaches a supersaturated state. The solution is allowed to stand at a constant temperature and grow at the target evaporation temperature. During the standing process, the solvent is kept in a volatile state until single crystal particles or agglomerated particles formed by single crystal particles grow at the bottom of the solution in the container and the side wall of the container, namely, boric acid oxazole particles. The cooling target temperature is lower than the dissolving target temperature.

6. The preparation method according to claim 5, characterized in that: When the constant temperature static growth is carried out at the cooling target temperature, the container containing the solution is kept sealed and no solvent is volatilized, the average size of the grown single crystal particles exceeds 1 mm, and the agglomerated particles formed by the single crystal particles are not less than 1 cm; The constant temperature static growth is carried out at the evaporation target temperature, the single crystal particle size is not less than 1mm, and the agglomerated particles formed by the single crystal particles are not less than 1cm.

7. The preparation method according to claim 5, characterized in that: The boron-containing compound is at least one of boric acid, boron trioxide or sodium borate; The solvent in step (1) is at least one of water, N,N-dimethylformamide, N,N-dimethylacetamide or ethylene glycol methyl ether.

8. A boron nitride material, characterized in that: The boron nitride material is obtained using the boric acid azole crystals described in any one of claims 1 to 4 or the boric acid azole particles obtained by the preparation method described in any one of claims 5 to 7 as raw materials.

9. The boron nitride material according to claim 8, characterized in that: The boric acid azole crystals according to any one of claims 1 to 4 or the boric acid azole particles obtained by the preparation method according to any one of claims 5 to 7 are dissolved in a solvent at a temperature range of 25-150° C. to form a boric acid azole solution with the boric acid azole particles as a solute and a concentration ranging from 1 wt.% to 15 wt.%; The solvent is at least one of water, formic acid, acetic acid, methanol, ethanol, isopropanol, DMAC, diethanolamine, triethanolamine, or propylene glycol, ethylene glycol, ethylene glycol methyl ether, dimethyl sulfoxide or tert-butyl alcohol; Add high molecular polymer to the boric acid azole solution and mix and dissolve to form a mixed liquid. The mass ratio of the mass of the high molecular weight polymer (in grams as a unit of measurement) to the mass of the mixed liquid formed (in grams as a unit of measurement) is in the range of 1wt.%-15wt.%; The mixed liquid is spun at a temperature range of 25-80° C. to form a continuous fiber precursor, and the precursor is pyrolyzed at a temperature range of 800-1600° C. for 1-4 hours in a nitrogen environment containing ammonia to obtain a continuous fiber material of boron nitride; The nitrogen environment with ammonia is a mixed gas environment of ammonia + nitrogen with an ammonia volume content ranging from 10 vol.% to 100 vol.%; Alternatively, the hexagonal boron nitride material is directly obtained by pyrolyzing the boric acid azole crystals described in any one of claims 1 to 4 or the boric acid azole particles obtained by the preparation method described in any one of claims 5 to 7 under a nitrogen inert environment.

10. The boron nitride material according to claim 9, characterized in that: The high molecular polymer is at least one of polyvinyl alcohol, polyethylene oxide, polyethylene imine, polyvinyl pyrrolidone, polyacrylonitrile, polycaprolactone, polyether sulfone, polyimide, chitosan, polyether ether ketone or cellulose; The boron nitride material is boron nitride foam or boron nitride fiber; Boric acid azole crystals have the property of melting into a fluid melt in the temperature range of 150-250°C; The solution of oxazole borate has the characteristic of changing into a viscous and fluid liquid state as the solvent evaporates within the temperature range of 90-250°C.

Citation Information

Patent Citations

  • Organic compound and organic light-emitting device using same

    CN113354624A

  • Preparation method of boron nitride spherical particles and boron nitride spherical particles

    CN116692789A

  • Preparation method of resin-assisted atomization molded boron nitride-based complex-phase spherical material

    CN118929586A

  • 4-amino-1, 2, 4-triazole nitrate second-order nonlinear optical crystal material and preparation and application thereof

    CN119082870A